Context and Linkage Strategies for Developing Innovation Management in the Thai Textile and Garment Industry - Infahsaeng, Anupong (Business Administration and Management Journal Review, 2022)
The main purposes of the research were 1) to study the strategic connection with the development of innovation in the Thai textile and garment industry and 2) to study the ability to create innovative management of Thai textile and garment enterprises. The sample of this research were 371 companies , using questionnaires as tool for data collection. Data were analyzed by quantitative methods. The descriptive statistics using frequency, percentage, mean and standard deviation. The analysis of variable element indicators was observed in the measurement model, using the Structural Equation Modeling (SEM. Preliminary data analysis It was found that most of them were medium-sized establishments 67.39 percent, Registered limited partnership 51.76 percent, Duration of business operations between 11-15 years 49.60 percent and Business that is sold in foreign countries 77.63 percent. The study showed that Strategic linkages of 1 variable from 5 variables . Is the Strategy 4. Develop marketing potential for textile and garment industry entrepreneurs With a positive overall influence of 0.0022 . The development of workplace management innovation is linked to 4 variables . Consists of 1) Product innovation 2) Process Innovation 3) Marketing Innovation and 4) Organization Innovation. With a positive overall influence equal to 0.01- 0.18.